Psychological correlates of perceived ethnic discrimination in Europe: a meta-analysis - De Freitas, D. F. (2018)
Objective: Many studies point to the negative impact of discrimination on the psychological and social functioning of ethnic minority persons. The realization of these studies across multiple European countries enables a systematization of this knowledge, which is our goal in the present work. Method: This study presents a systematic review and a meta-analysis of the correlates of perceived ethnic discrimination among ethnic minority persons living in European countries. Results: The analyses of 121 effect sizes reveal that discrimination is positively associated with symptoms of psychiatric disturbances, depression, psychosis, perceived stress, and externalizing behavior. Discrimination is also negatively associated with the self-esteem, positive evaluation of life, self-efficacy/mastery, well-being, and psychological adaptation of migrants. The results show that the strength of these relationships is, in some cases, moderated by persons' gender, age, and ethnicity and countries' multicultural preference and countries' rating in the Migrant Integration Policies Index (MIPEX), namely, in regard to labor market mobility, permanent residence, and antidiscrimination policies. Conclusions: The detrimental effect of discrimination on many psychosocial dimensions emphasizes the need for governmental agencies to develop systemic and concrete interventions to decrease ethnic prejudice in Europe. Moreover, the results show that fostering multiculturalism, and implementing broad antidiscrimination policies has a protective function in the face of discrimination. Enforcing the implementation of these policies can be a fundamental way to promote the psychological adjustment of ethnic minority persons.